Operative vaginal deliveries – are midwives safer practitioners? a retrospective cohort study. (18th April 2012) - Black, M; Mitchell, E; Danielian, PJ
Abstract : Introduction: Specialist midwife roles have extended to include operative vaginal delivery (OVD). It may be hypothesised that a midwives' experience of normal childbirth enhances her ability to mimic spontaneous birth during OVDs. Our aim was to compare outcomes of midwife-performed OVDs with those performed by doctors. Methods: The maternity data management system was used to identify cases in Aberdeen between June 2005 and June 2010. Those delivered by midwives formed the exposed cohort. Obstetric outcomes were initially compared with those performed by any doctor, and in a secondary analysis, with those by junior doctors (ST3 to ST5 or equivalent) only. Fisher's exact test, backward logistic regression analysis and independent sample T-tests were used in the statistical analyses where appropriate. Results: Of 2540 women, 330 were delivered by midwives and 2210 by doctors, of whom 1049 were by junior doctors. Patient characteristics were comparable in each group. Women were no more likely to obtain a third or fourth degree tear when their delivery was performed by a midwife than those performed by a doctor (adj OR 0.6 95% C.I 0.3-1.2), or junior doctors specifically (adj OR 0.6 95% C.I 0.3-1.2). Mean blood loss was significantly less when compared with all doctors (mean difference -57ml p=0.03.), but no significant difference was found when compared with junior doctors (mean difference -43ml p=0.1). Conclusion: Once adjusted for mode of delivery, extended perineal injury and mean blood loss were similar in each group. Midwives were significantly less likely to use forceps as their instrument of choice.